Giant Megaureter by Intramural Ureteral Etopia in a Bitch - Martins Coelho, Mylena; de Oliveira Ribeiro, Juliana; Neves Boeloni, Jankerle; Rodrigues Rosado, Isabel; Martin, Ian; Garcia Lopes, Matheus; Sampaio Linhares, Renato; Gabellini Leonel Alves, Endrigo (Acta Scientiae Veterinariae, 2023)
Background: The urinary tract is composed by kidneys, urinary bladder and urethra. The kidneys produce urine that achieve urinary bladder by ureters. These have the origin in the renal pelvis, run through the retroperitoneum, end up at the dorsolateral superficies of the urinary bladder, and empty at the trigone. Ureters abnormalities are the rarest congenital defects in the canine urinary tract and ureteroceles are cystic dilatations of the distal segment of the ureter that could be associated to partial or complete urinary obstructions and could lead to megaureter and hydronephrosis. So, the aim of the present study was to describe a case of megaureter by intramural ureteral ectopia in a bitch. Case: A 1-year-old-and-8-month bitch Akita, weighing 18 kg, was referred to the Uniube Veterinary Hospital with vaginal secretion, prostration, hypodipsia, hyporexia and pyrexia related by the tutor. On physical examination, an increase in vulva volume and a vaginal discharge were observed. Nevertheless, others physical exams, blood count and biochemical tests were considered to be within normal parameters. Urinalysis showed cloudy aspect, proteinuria, occult blood, erythrocytes, pyuria, leucocytes, and discreet presence of bacteria. Abdominal ultrasonography revealed a megaureter with right uterocele and excretory urography showed absence of glomerular filtration by right kidney. The patient was submitted to surgery for right kidney and ureter exeresis. Histopathology evaluation showed intense dilation of the ureter and severe multifocal renal fibrosis. The surgery was well succeeded, and the patient recovered completely. Discussion: Once megaureter are associated with congenital abnormalities like ectopic ureter and ureterocele, it is usually diagnosed in young patients with medium age of 10 months, which is below the age of the patient in this case report. Additionally, in the patient here reported, the unilateral alteration could explain the absence of kidney fail symptoms. In more than 90% of the cases, the ureteral ectopia was associated with multiple anomalies in the urinary tract, as was observed in this patient, that presented besides ectopic ureter, ureterocele, megaureter and renal dystrophy. All these morphological alterations made impossible the complete urine elimination, which predispose to urinary tract infection, that was observed in this report. According to literature, urinary tract anomalies are associated with infection in 64 to 85% and 50% of the cases also present hydronephrosis and hydroureter. It was also described that ureteral ectopia is diagnosed by visualization of hydroureter in abdominal ultrasonography. The findings present in this report differs a little, once the right kidney was atrophic possibly by malformation or even so by a chronic renal lesion due to the difficulty in urine flow. The excretory urography showed no filtration in the right kidney, indicating non-functionality that was confirmed by histopathology, in which was observed small glomerulus and large amount of connective tissue deposition. In cases of unilateral megaureter with ipsilateral kidney commitment, there is indication of nephroureterectomy, that was performed in the patient of the present report. As far as we know, this is the first report of megaureter, ureterocele and ectopia ureteral together in the same patient. In conclusion, the procedure was secure, efficient and promote a better quality of life for the patient and prevent the recurrence of urinary tract infections. Keywords: Urinary system, malformation, nephroureterectomy, surgery, cystitis. Título: Megaureter gigante por ectopia ureteral intramural em cadela. Descritores: Sistema urinário, malformação, nefroureterectomia, cirurgia, cistite. ystitis.